Perlindungan Hukum bagi Kreditor Separatis terkait dengan Penolakan Perdamaian dalam Proses PKPU - Rinaldi; Yuhelson, Yuhelson; Hakim, Nur (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2025)
The objective of this thesis is: 1) To analyze the position and rights of creditors who reject the peace proposal in the PKPU process based on the applicable laws and regulations in Indonesia. 2) To analyze the form of legal protection and its implementation for creditors who reject the peace proposal in the PKPU process. The research method used is normative research, where the researcher connects the study with the prevailing laws and regulations. The results of this thesis research are: 1) That creditors have different legal positions in the PKPU process, especially the secured creditors who hold a special position because they retain the right to execute the collateral object and are still protected even if they reject the composition plan proposal that approved by the majority of creditors. The law also ensures that the secured creditors' property rights are not nullified by the decision of the majority of creditors. Therefore, the PKPU legal system in Indonesia has accommodated legal protection for creditors who reject the composition plan proposal during the PKPU process. 2) UUK-PKPU provides legal protection instruments for secured creditors who reject the composition plan proposal, through Article 281 paragraph (2) which grants the right to compensation, and Article 286, which states that the secured creditors who reject the composition plan proposal are not bound by the ratified composition plan proposal. These two articles aim is to ensure that the rights of secured creditors are protected during the PKPU process. However, in practice, the implementation of these provisions still shows inconsistencies, as seen in the cases of PT Adhi Persada Properti vs. PT Bank Jtrust Indonesia;as well as the case of PT K88 vs. its’ Secured Creditors. This phenomenon caused by the judges' lack of understanding, as they only refer to Article 281 paragraph (2) and disregard the Article 286 UUK-PKPU, whereas these two articles must be applied together to provide comprehensive legal protection for secured creditors who reject the composition plan proposal in the PKPU process. Therefore, the researcher argues that improvements are needed in the provisions that protecting the secured creditors who reject the composition plan proposal in PKPU, by clarifying the compensation mechanism and ensuring the close relations between Article 281 paragraph (2) and Article 286 UUK-PKPU. Additionally, there should be an enhancement for judges' understanding of applying both articles through training and special guidance from the Supreme Court to avoid the legal uncertainties and misinterpretation in judicial decisions.